Development of enteric-coated microspheres of embelin for their beneficial pharmacological potential in ulcerative colitis. (18th August 2017) - Nidhi,; Dadwal, Ankita; Hallan, Supandeep Singh; Sharma, Saurabh; Mishra, Neeraj
Abstract: The aim of the present study is to develop embelin-loaded enteric-coated microspheres and investigate their pharmacological potential in acetic acid induced ulcerative colitis. The optimized formulation of embelin-loaded microspheres has shown significant sustained release of embelin. Further this formulation significantly reduced the ulcer activity score and oxidative stress, and attenuated the inflammatory changes. Thus it may be concluded that embelin-loaded enteric-coated microspheres have shown delayed release capacity than plain embelin and exerts colon ulcer protective effect in rats.